Comparative assessment of drug-eluting balloons in an advanced porcine model of coronary restenosis - Joner, Michael; Byrne, Robert A.; Lapointe, Jean-Martin; Radke, Peter W.; Bayer, Gerd; Steigerwald, Kristin; Wittchow, Eric (Thrombosis and Haemostasis, 2011)
The advent of drug-eluting balloon (DEB) therapy has represented an important development in interventional cardiology. Nevertheless, pre-clinical data with this technology remain scant, and comparative studies have not previously been published. Bare metal stents were implanted in the coronary arteries of 15 pigs followed by balloon angioplasty. Animals were allocated to treatment with a 60-second inflation of one of four different balloon catheters: a conventional untreated plain angioplasty balloon (PBA, Biotronik AG), the Pantera Lux DEB (3.0 μg/mm2 paclitaxel; BTHC excipient, Biotronik AG), the Elutax DEB (2.0 μg/mm2 paclitaxel; no excipient; Aachen Resonance), or the SeQuent Please DEB (3.0 μg/mm2 paclitaxel; iopromide excipient: B. Braun). Twenty-eight days following balloon deployment, animals underwent repeat angiography for quantitative coronary angiography analysis and euthanasia for histopathologic assessment. By histology, the mean neointimal thickness was 0.44 ± 0.19 mm with PBA, 0.35 ± 0.13 mm with Pantera Lux, 0.61 ± 0.20 mm with Elutax, and 0.47 ± 0.21 mm with SeQuent Please DEB (p=0.02). In comparison with PBA, deployment of the Pantera Lux or the SeQuent Please DEB resulted in delayed healing characterised by significant increases in fibrin, neointimal cell vacuity and delayed re-endothelialisation. In conclusion, investigation of comparative DEB performance in a porcine model of advanced coronary restenosis reveals significant heterogeneity of neointimal suppression between the devices tested with numerically lowest values seen in the Pantera Lux group. On the other hand, evidence of delayed healing was observed in the most effective DEB groups.
Keywords: Porcine model; drug-eluting balloon; restenosis